2018
DOI: 10.1589/jpts.30.307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a physiotherapy rehabilitation program on knee osteoarthritis in patients with different pain intensities

Abstract: [Purpose] To examine the effect of physiotherapy rehabilitation program on moderate knee osteoarthritis in patients with different pain intensities. [Subjects and Methods] Sixty subjects (37 men and 23 women) with moderate knee osteoarthritis participated in the current study. Randomization software was used to select the participating subjects’ numbers from the clinic records. They were classified into three groups according to pain intensity: mild, moderate, and severe pain groups. All groups underwent a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…A previous study revealed the beneficial effect of pre‐emptive PEMF exposure on cartilage degeneration and subchondral bone loss for knee OA (KOA) in rats, and that the time point of treatment initiation is significant for treating OA [Yang et al, 2017]. Besides, clinical studies showed that PEMF can provide benefits for KOA patients in relieving pain and stiffness, and improving physical function and quality of life [Bagnato et al, 2016; Abdel‐Aziem et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed the beneficial effect of pre‐emptive PEMF exposure on cartilage degeneration and subchondral bone loss for knee OA (KOA) in rats, and that the time point of treatment initiation is significant for treating OA [Yang et al, 2017]. Besides, clinical studies showed that PEMF can provide benefits for KOA patients in relieving pain and stiffness, and improving physical function and quality of life [Bagnato et al, 2016; Abdel‐Aziem et al, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…At one end of the scale, it is marked as "no pain" and at the other end, it is marked as "extreme pain" [10]. Similarly, muscle strength was measured by using manual muscle testing (MMT) of quadriceps and hamstrings muscles before and after the treatment, in a standardized protocol as reported by Kendall [11].…”
Section: Protocolmentioning
confidence: 99%
“…Slow reversalhold: Slow reversal hold is defined as an "isotonic contraction of the agonist followed immediately by an isotonic contraction of the antagonist" [10]. The patient was laid down in a prone position, with the knee in extension and the hip in 0 degrees of rotation, abduction, and adduction.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis (OA) (Latin: arthrosis, osteoarthritis, osteoarthrosis) constitutes a common cause of necessity for using rehabilitation benefits by seniors [1][2][3]. It is the most common disease of the locomotor system, and its prevalence increases with age [4][5][6].…”
Section: Introductionmentioning
confidence: 99%